2021
DOI: 10.1162/netn_a_00197
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale dynamic mean field (MDMF) model relates resting-state brain dynamics with local cortical excitatory–inhibitory neurotransmitter homeostasis

Abstract: Previous computational models have related spontaneous resting-state brain activity with local excitatory−inhibitory balance in neuronal populations. However, how underlying neurotransmitter kinetics associated with E-I balance governs resting state spontaneous brain dynamics remains unknown. Understanding the mechanisms by virtue of which fluctuations in neurotransmitter concentrations, a hallmark of a variety of clinical conditions relate to functional brain activity is of critical importance. We propose a m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 74 publications
(117 reference statements)
4
50
0
Order By: Relevance
“…However, our study departs significantly from these earlier theoretical frameworks in providing a more neurobiologically grounded mechanism of multisensory integration based on the existence of balanced states of higher segregation and decreased global integration (Lord et al, 2017) employed by nodes of the PBN. In light of our current results and previous modeling studies (Abeysuriya et al, 2018;Naskar et al, 2021;Vattikonda et al, 2016), we propose that balanced states of functional integration and segregation may emerge from the underlying excitatory-inhibitory (E-I) balance in local neuronal populations of involved brain areas and may even be related to neurotransmitter homeostasis (Naskar et al, 2021;Shine et al, 2021). While spontaneous brain activity such as during resting state has been typically associated with the E-I balance (Abeysuriya et al, 2018;Naskar et al, 2021;Vattikonda et al, 2016), the potential of altered E-I balance-in guiding the formation of perceptual experience from interactions between inclement sensory signals with stored associative memories (Barron et al, 2017), as a catalyst for volitional control effectuating perceptual stability (Kondo et al, 2018), in guiding decision making strategies during multi-attribute choice (Pettine et al, 2021); all have been proposed recently.…”
Section: Discussionsupporting
confidence: 80%
“…However, our study departs significantly from these earlier theoretical frameworks in providing a more neurobiologically grounded mechanism of multisensory integration based on the existence of balanced states of higher segregation and decreased global integration (Lord et al, 2017) employed by nodes of the PBN. In light of our current results and previous modeling studies (Abeysuriya et al, 2018;Naskar et al, 2021;Vattikonda et al, 2016), we propose that balanced states of functional integration and segregation may emerge from the underlying excitatory-inhibitory (E-I) balance in local neuronal populations of involved brain areas and may even be related to neurotransmitter homeostasis (Naskar et al, 2021;Shine et al, 2021). While spontaneous brain activity such as during resting state has been typically associated with the E-I balance (Abeysuriya et al, 2018;Naskar et al, 2021;Vattikonda et al, 2016), the potential of altered E-I balance-in guiding the formation of perceptual experience from interactions between inclement sensory signals with stored associative memories (Barron et al, 2017), as a catalyst for volitional control effectuating perceptual stability (Kondo et al, 2018), in guiding decision making strategies during multi-attribute choice (Pettine et al, 2021); all have been proposed recently.…”
Section: Discussionsupporting
confidence: 80%
“…At a more fundamental level, 1/f scale reflects the self-similar temporal properties of the self-organized critical states. Although the aim of this study is not to resolve this debate, however, we argue that 1/f activity could arise from potentially number of factors, e.g., altered tissue properties or self-organized criticality and transient stability with aging and change in underlying excitation-inhibition (E/I) balance ( Bédard et al, 2006 ; Voytek et al, 2015 ; Gao et al, 2017 ; Naik et al, 2017 ; Naskar et al, 2021 ).…”
Section: Discussionmentioning
confidence: 95%
“…Building on these foundations, further research demonstrated that the same homeostatic mechanisms rendered cortical networks more robust to changes in parameters such as transduction delays and global coupling strength ( Abeysuriya et al, 2018 ). Interestingly, in a recent study, using an updated model of coupled excitatory and inhibitory populations with a term that quantifies the concentration of excitatory and inhibitory neurotransmitters at a local level, it was found that there are optimal concentrations of glutamate and GABA that maximize fit of simulated and empirical FC ( Naskar et al, 2021 ). Not only that, but these suggested optimal concentrations also corresponded to a working point of activity where the brain is in a state of heightened metastability.…”
Section: Large Scale Modeling Of the Human Cortex: Excitatory-inhibitory Balance And Strokementioning
confidence: 99%